Robust and efficient reranking in crystal structure prediction: a data driven method for real-life molecules - Anelli, Andrea; Dietrich, Hanno; Ectors, Philipp; Stowasser, Frank; Bereau, Tristan; Neumann, Marcus; Ende, Joost van den (CrystEngComm, 2024)
We accelerate a key step in crystal structure prediction (CSP) using machine learning and report its robustness on a wide array of pharmaceutical molecules. The speedup achieved by our scheme allows for a scale-up in both the number of candidate drug molecules studied and the level of theory employed in their treatment, paving the way for tackling more complex crystal energy landscapes.